IDENTIFICATION OF ETHNOMEDICINAL COMPOUNDS AND ANTIMICROBIAL STUDIES OF SALVADORA PERSICA L. (SALVADORACEAE) - PRABHAKARAN K; JOHN BRITTO S; PREETHI J (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Salvadora persica L. is a dense foliaceous evergreen shrub or small tree with diversified medicinal properties. The objective of this work was to do a comparative study on phytochemical composition between different plant parts of S. persica collected from the southern region of India. Methods: The phytochemical analysis of ethyl acetate fraction of ethanolic extracts from leaves, tender stems and tree bark of S. persica was done by gas chromatography-mass spectrometry/mass spectrometry (GC-MS/MS). Also, the anti-bacterial and anti-fungal activity of extracts was analyzed in vitro by Disc-diffusion method. Results: GC-MS/MS analysis of S. persica showed 29 phytocompounds. Among them, except for eugenol, caryophyllene, benzyl isothiocyanate, oleic acid, and fatty acid, the remaining 24 phytocompounds were newly reported in the present study. For the first time, a maximum amount of benzyl isothiocyanate (73.5%) was identified from tree bark extract of S. persica and this extract showed higher in vitro antimicrobial activity against gram-positive, gram-negative bacteria and fungi than leaves and tender stems. Conclusion: The study demonstrated that benzyl isothiocyanate could be the major antimicrobial component in S. persica.